The Effect of Classroom Management and Teacher Work Ethics on the Effectiveness of the Teaching and Learning Process - Kontesa, Emilia; Fitria, Happy; Puspita, Yenny (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aimed to describe the effect of classroom management and teacher work ethic partially and simultaneously on the effectiveness of the teaching and learning process. This study used a quantitative method with a correlational approach. Population of the study were 703 teachers of SMA Negeri OKU Selatan Regency. Sample of the study was 137 teachers. Technique collecting data used was by distributing questionnaires to respondents. Data were analyzed by using multiple linear regression, partial correlation and multiple correlation. This study resulted in the conclusions (1) There was an effect of classroom management on the effectiveness of the teaching and learning process; (2) There was an effect of the work ethic of the teacher on the effectiveness of the teaching and learning process; and (3) There was an effect of classroom management and the work ethic of teachers simultaneously on the effectiveness of the teaching and learning process.